The Development of Digital Flipbook Media Based on the 5 Hours Battle of Kalianda upon High School History Materials - Bahtiar Afwan; Nunuk Suryani; Deny Tri Ardianto (Budapest International Research and Critics University, 2020)
The purpose of this study is to develop a digital flipbook learning media by integrating the local history material of ‘The 5 Hours Battle of Kalianda’ in one of the high schools in Kalianda City. This study uses research and development (R&D) as the research methods. The stages of the research include: the stages of analysis, design, development, implementation, and evaluation. The subjects in this study consisted of two material and two media experts as validator, 40 eleventh-graders students, and a history teacher. The results of the study showed that the Flipbook digital media based on ‘The 5 Hours Battle of Kalianda’ had proven to be valid and feasible according to the material and media expert assessments, while the results of small group trials, limited group trials, and extensive trials indicated digital Flipbook learning media based on ‘The 5 Hours Battle of Kalianda’ was proven to be effective and suited with the needs analysis.